Enhanced Resting-State Functional Connectivity of the Nucleus Accumbens in First-Episode, Medication-Naïve Patients With Early Onset Schizophrenia - Cao, Xiaohua; Li, Qiang; Liu, Sha; Li, Zexuan; Wang, Yanfang; Cheng, Long; Yang, Chengxiang; Xu, Yong (Frontiers in Neuroscience, 2022)
There is abundant evidence that early-onset schizophrenia (EOS) is associated with abnormalities in widespread regions including cortical, striatal and limbic areas. As a main component of the ventral striatum, the nucleus accumbens (NAc) has been implicated in the pathology of schizophrenia. However, functional connection patterns of NAc in patients with schizophrenia, especially EOS, is seldom explored. Seventy-eight first-episode medication-naïve patients with EOS and 90 healthy controls (HCs) were recruited in the present study, and resting-state seed-based functional connectivity (FC) analysis were performed to investigate temporal correlations between NAc and the rest of the brain in the two groups. Additionally, correlation analyses were done between regions showing group difference in NAc functional integration and clinical features of EOS. Group comparison found enhanced FC of the NAc in the EOS group relative to the HCs, with increased FC in right superior temporal gyrus and left superior parietal gyrus with the left NAc-region of interest (ROI), and elevated FC in left middle occipital gyrus with the right NAc-ROI. No significant association were found between FC strength and symptom severity as well as the age of the patients. Our findings revealed abnormally enhanced FC of the NAc with regions located in the temporal, parietal and occipital areas, which were implicated in auditory/visual processing, sensorimotor integration and cognitive functions. The results suggest disturbed relationships between regions subserving reward, salience processing and regions subserving sensory processing as well as cognitive functions, which may deepen our understanding about the role of NAc in the pathology of EOS.